Bleeding outcomes with ticagrelor versus clopidogrel in patients with acute coronary syndrome. A focused analysis from the multicenter CREA-ARIAM Andalucia registry. (2nd May 2022) - Padilla Rodriguez, G; Hernandez-Meneses, BG; Gomez-Gonzalez, A; Carmona-Carmona, J; Garcia-Gonzalez, N; Arboleda Sanchez, JA; Rodriguez Yanez, JC; Soto Blanco, JM; Fernandez Garcia, I; Castillo Caballero, JA; Hidalgo-Urbano, RJ; Garcia-Rubira, J C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): The study project was financially supported by a no conditional grant (AstraZeneca) Background/Introduction: With the advent of more potent antithrombotic agents, bleeding has emerged as an important safety concern in patients with acute coronary syndrome (ACS). Moreover, hemorrhagic complications have been strongly linked with subsequent mortality in this clinical scenario. Purpose: We sought to determine the incidence, types, timing and prognostic relevance of major bleeding events in ACS patients treated with ticagrelor or clopidogrel in contemporary practice. Methods: Prospective, observational, multicentre all-comers registry of ACS patients who were intended to receive a 12-month DAPT course with ticagrelor or clopidogrel. Major bleeding was defined as a type 3 or 5 bleed using the Bleeding Academic Research Consortium (BARC) definition. Bleeding was further classified according to the anatomic location. All bleeding episodes were analysed accounting for death as a competing event, using competing risk regression models based on the on-treatment principle (i.e., according to the P2Y12 inhibitor actually received from date of index admission until either time of DAPT cessation plus 14 days or censoring, whichever occurred first). Results: Among 2070 patients surviving to hospital discharge (mean age 63 years, 27% women, 62.5% STEMI), 106 (5.3%, 0.6%/year) experienced major bleeding event at a median time of 92 days (interquartile range, 6–187 days) after discharge. Most events (n=59, 55.7%) were BARC type 3a bleeds with 2 fatal bleeds (type 5b). In most cases (53%), the site of bleeding was gastrointestinal, followed by intracranial (n=13, 12%). After adjustments for baseline predictors, ticagrelor was associated with increased but not statistically significant risk of major bleeding compared with clopidogrel (5.6% vs 5.2%, adjusted hazard ratio [aHR] 1.40, 95% CI 0.96 – 2.05; P = .075). Major bleeding was significantly associated with nearly 2-fold higher risk of mortality (aHR 1.94; 95% CI 1.32– 2.86; P = .001), irrespective of P2Y12 inhibitor treatment (P interaction = .159). Conclusion(s): Bleeding was not rare within 1 year after index ACS, with incidence rates peaked at 30 to 60 days post-index admission. The most common bleeding site was gastrointestinal followed by intracranial haemorrhage. Ticagrelor use was not associated with significantly increased risk of major bleeding compared with clopidogrel whereas bleeding led to a nearly 2-fold higher risk of major bleeding.